2008
DOI: 10.1167/iovs.07-0984
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxidative Stress in Trabecular Meshwork Cells Are Reduced by Prostaglandin Analogues

Abstract: Oxidative stress is able to induce characteristic glaucomatous TM changes in vitro, and these oxidative stress-induced TM changes can be minimized by the use of prostaglandin analogues. Thus, prevention of oxidative stress exposure to the TM may help to reduce the progression of POAG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
5

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(58 citation statements)
references
References 49 publications
2
51
0
5
Order By: Relevance
“…This observation can be explained not only by the effect of active substances, but also by BAK action. Many other in vitro studies have shown that preservatives are cytotoxic, especially for the cells of the ocular surface: conjunctival and corneal epithelium and keratocytes [7,9,14,[16][17][18][19] but also for the deeper ocular tissues (fibroblast of Tenon's capsule, cells of lens epithelium and trabecular meshwork) [15,20]. Although the cytotoxic effect of BAK is well documented in patients [15] and on cultivated adherent cells, its influence on lymphocytes seems not to have been explored until this study.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation can be explained not only by the effect of active substances, but also by BAK action. Many other in vitro studies have shown that preservatives are cytotoxic, especially for the cells of the ocular surface: conjunctival and corneal epithelium and keratocytes [7,9,14,[16][17][18][19] but also for the deeper ocular tissues (fibroblast of Tenon's capsule, cells of lens epithelium and trabecular meshwork) [15,20]. Although the cytotoxic effect of BAK is well documented in patients [15] and on cultivated adherent cells, its influence on lymphocytes seems not to have been explored until this study.…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…Huge differences in these concentrations are probably due to differences in methods of cell treatments by BAK (especially in treatment and recovery time) and sensitivities of assays. Trabecular meshwork cells also seem to be very sensitive to BAK stimulation: in concentrations as low as 0.00015%, it kills about 20% of cells [20].…”
Section: Discussion Discussion Discussion Discussionmentioning
confidence: 99%
“…In addition, iodine has proven to significantly decrease malondialdehyde (MDA) in animal models of abdominal aortic I/R (26), induce liver peroxidation (27), and reduce hydrogen peroxide-induced pathological glaucomatous changes in cultured cells (28).…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown to possess a number of biological effects in addition to its well-known vasoactive activity (23). These include cell proliferation, differentiation, and oxidative stress-induced cell death inhibition (24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%